Hormones et reconfiguration des identités sexuelles au Brésil - Sanabria, Emilia (Clio. Femmes, Genre, Histoire, 2013)
Les hormones sexuelles sont des objets hybrides et complexes à la frontière du sexe et du genre. Dès lors qu’elles sont synthétisées sous forme pharmaceutique, elles peuvent attribuer des caractéristiques sexuelles au corps de manière partiellement exogène à celui-ci. Il s’en suit que l’utilisation clinique qui en est faite est socialement réglementée. À travers une analyse de divers contextes d’utilisation des hormones observés à Bahia, au Brésil, cet article montre que le dualisme sexuel est le produit de pratiques de régulation biomédicales qui visent à encadrer la circulation des hormones. Le sens du terme local « hormônio » n’est pas pleinement recoupé par celui d’hormone, qu’il excède. L’emploi commun qui est fait au Brésil du singulier procure au terme « hormônio » une qualité fluide et homogène. Dans ce contexte, les hormones sont comprises comme une sorte de substance qui peut circuler entre les corps. Cette conceptualisation des hormones comme une substance a des implications pour le statut ontologique des corps et révèle la relative plasticité de la relation sexe/genre.
ISBN: 9782701177816 Number: 37 Publisher: Éditions Belin
Keywords: 1900-1999; 1950-1959; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du sud; amériques; approches et analyses; brésil; corps; cours; discipline; discours dominant; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques

Gay and lesbian literature in the classroom: Can Gay themes overcome heteronormativity? - April M Sanders; Janelle B. Mathis (Journal of Praxis in Multicultural Education, 2013)
Lesbian, gay, bisexual, and transgender (LGBT) characters do exist in children’s and young adult literature, yet there is a lack of classroom exposure to such literature. Educational organizations have realized the need for dispelling prejudices about LGBT people by including such texts in the classroom as well as discussions regarding LGBT themes and characters in the books. Yet the practice of simply including diverse texts without discussing LGBT issues could cause greater marginalization for students because the silence regarding LGBT issues and characters encourages the practice of heteronormativity. This inquiry examined a range of children’s and adolescent books that could be used in classroom discussions to develop insight about LGBT themes and characters in order to understand if the texts were saturated with LGBT themes and characters to the point that teachers and students could not avoid the LGBT factors while reading.
Keywords: amériques; approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; pédagogie; ressource en ligne; régions géographiques; science de l'éducation; systèmes d'oppressions; thématiques; états-unis

Creating comprehensive, youth centered, culturally appropriate sex education: What do young gay, bisexual, and questioning men want? - Pingel, Emily Sweetnam; Thomas, Laura; Harmell, Chelsea; Bauermeister, José A. (Sexuality Research and Social Policy, 2013)
We examined young gay, bisexual and questioning men's (YGBQM) experiences with school-based sex education as they sought to learn about sex and sexual health, and their suggestions for improving same-sex education resources. Thematic analysis of 30 in-depth interviews with YGBQM (ages 18-24) underscored the discrepancies between the existing school-based sex education curricula and YGBQM's perceived sex education needs. Our results show that many youths' sexuality and same-sex sexual behaviors are excluded in sex education lessons; however, YGBQM noted that they sought out other resources (e.g., websites) to answer their questions. We discuss YGBQM's ideas for the creation of a sex and sexual health website that would be tailored for youth like themselves, including topics and features that an ideal website would contain. In addition, we present recommended changes to existing school-based sexual education curricula.
Keywords: EDI; LGBTQIA2+; amériques; approches et analyses; hétérosexisme; identités LGBTQIA2+; jeunes adultes; ressource en ligne; régions géographiques; santé; santé sexuelle; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; états-unis; étude qualitative

L’inclusion de la diversité sexuelle à l’école : les enjeux pour les élèves lesbiennes, gais, bisexuels et en questionnement - Richard, Gabrielle; Chamberland, Line; Petit, Marie-Pier (Revue canadienne de l’éducation, 2013)
Cet article s'appuie sur les résultats d'une enquête qualitative menée auprès de 65 jeunes lesbiennes, gais, bisexuels et en questionnement (LGBQ) québécois qui ont témoigné de leurs expériences scolaires en lien avec l'homosexualité. Les entrevues visaient à rendre compte de la place de la diversité sexuelle dans les cours, à relever les façons dont est abordée cette thématique en classe, ainsi qu'à examiner les perceptions qu'ont les participants de ces moments de visibilité. Les jeunes LGBQ rapportent que les sujets relatifs à la diversité sexuelle sont rarement abordés à l'école, mais se souviennent avec force détails de chacune des mentions de ces sujets. Nombre d'entre eux rapportent une vive crainte d'être étiqueté comme homosexuel à l'occasion de telles séances, ou encore de faire l'objet de railleries homophobes par la suite.
Number: 1
Keywords: 2000 à aujourd'hui; 2000-2009; EDI; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; discipline; discours dominant; homophobie; hétérosexisme; identités LGBTQIA2+; périodes historiques; québec; ressource en ligne; régions géographiques; science de l'éducation; systèmes d'oppressions; systèmes éducatifs; thématiques; école; étude qualitative

Race, gender, class, sexuality (RGCS) and hypertension - Veenstra, Gerry (Social Science & Medicine, 2013)
Informed by intersectionality theory, a tradition that theorizes intersecting power relations of racism, patriarchy, classism and heterosexism, this paper investigates the degree to which race, gender, class and sexuality manifest distinct and interconnected associations with self-reported hypertension in nationally-representative survey data from Canada. Binary logistic regression is used to model the main effects of, and interactions between, race, gender, education, household income and sexual orientation on hypertension, controlling for age, using data from the 2003 Canadian Community Health Survey (n = 90,310). From a main effects (‘additive’) perspective, Black respondents, respondents with less than high school and poorer respondents were significantly more likely than White respondents, university-educated Canadians and wealthier Canadians, respectively, to report hypertension. However, the interactive models indicate that the additive models were poor predictors of hypertension for wealthy Black men, wealthy South Asian women, women with less than a high school diploma and wealthy bisexual respondents, who were more likely than expected to report hypertension, and for poor Black men, poor South Asian women, poor South Asian men and women with a university degree, who were less likely than expected to report hypertension. It appears that, with regard to blood pressure at least, Canadians experience the health effects of education differently by their genders and the health effects of income differently by their identities defined at the intersection of race and gender. This study provides empirical support for the intersectional approach to cardiovascular health inequalities by demonstrating that race, gender, class and sexuality cannot be disentangled from one another as predictors of hypertension.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; discipline; hétérosexisme; intersectionnalité; médecine; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé cardiovasculaire; sciences; sexisme; systèmes d'oppressions; thématiques